Prevalence of Periodontal Diseases among Patients Attending the Outpatient Department at the College of Dentistry, King Khalid University, Abha, Saudi Arabia (City Dental College Journal, 2018)
Aims: A retrospective study was performed involving 2739 patients who were attending the College of Dentistry outpatient clinic department of King Khalid University (KKU), Abha, Kingdom of Saudi Arabia (KSA) during the period of 1st January to 31st December, 2009. Methods: Random data were collected from the patients record files ofthe College of Dentistry who attended from 1st January to 30th December, 2009. Results: Among 2739 patients mean age 32±13 (range 11~82) years, males 86.5% and females 13.5%, were found sufferers of different types of periodontal diseases i.e., gingivitis and periodontitis. Gingivitis cases were found 1722(63.2%), in which mild gingivitis was 49.8%, moderate gingivitis 45.8%, severe gingivitis 1.97%, acute gingivitis 0.52% and puberty gingivitis 1.80%. Total number of patients affected with various forms of periodontitis was 1009 (36.8%), in which mild periodontitis was 57.4%, moderate periodontitis 36.6%, severe periodontitis 4.95% and aggressive periodontitis 0.89%. The prevalence and severity of gingivitis was found increased with age to a peak in the 21~30 years age group, whereas, periodontitis increased significantly (p